Differentiation between Trypanosoma cruzi and Trypanosoma rangeli using heat‐shock protein 70 polymorphisms. Issue 2 (13th November 2013) - Fraga, Jorge; Fernandez‐Calienes, Aymé; Montalvo, Ana Margarita; Maes, Ilse; Dujardin, Jean‐Claude; Van der, Gert
Abstract Objective Differential diagnosis of infection with Trypanosoma cruzi or T. rangeli is relevant for epidemiological studies and clinical practice as both species infect humans, but only T. cruzi causes Chagas' disease. Their common antigen determinants complicate the distinction between both species, while current PCR assays used for differentiation show some drawbacks. We developed and validated a generic PCR discriminating the species by restriction fragment length polymorphism (RFLP) analysis and a duplex PCR specifically amplifying a differently sized fragment of both species. Methods The assays are based upon a partial region of the heat‐shock protein 70 gene (hsp70). The analytical sensitivity and specificity were determined for both PCRs. The assays were analytically evaluated on a panel of six T. cruzi, one T. cruzi marinkellei and four T. rangeli strains, various other infectious pathogens, a panel of spiked samples of T. cruzi, and artificially mixed infections of T. cruzi and T. rangeli. Finally, the tools were applied on 36 additional isolates of Trypanosoma species. Results The detection limit of the PCRs was between 0.05 and 0.5 parasite genomes, and 1–10 parasites spiked in 200 μl blood. In artificial mixtures, PCR–RFLP picked up both species in ratios up to 102 and duplex PCR up to 104. In the 36 isolates tested, both single and mixed infections were identified. All assays were shown to be specific. Conclusion Our PCRs show high potential for the differential diagnosis of T. cruzi and T. rangeli, which in view of their sensitivity can aid in the confirmation of infection with these parasites in vectors, reservoirs and clinical samples.